2021
DOI: 10.1371/journal.pone.0252105
|View full text |Cite
|
Sign up to set email alerts
|

Outcome expectancies moderate the association between worry about climate change and personal energy-saving behaviors

Abstract: This paper explores whether efficacy beliefs can alter the relationship between worry about climate change and personal energy-saving behaviors, controlling for climate change beliefs and socio-demographics. For this purpose, we used data from 23 countries that participated in the European Social Survey Round 8 (N = 44 387). Worry about climate change, personal efficacy, personal outcome expectancy, and collective outcome expectancy were each associated with personal energy-saving behaviors concerning either e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 72 publications
(100 reference statements)
2
18
0
Order By: Relevance
“…Respondents were asked “To what extent do you feel that your own personal actions can help prevent [coronavirus from spreading/climate change from worsening]” in order to measure respondents’ perceived efficacy (also known as ‘outcome expectancy’, Gregersen et al, 2021 ). A similar end-labelled 11-point scale, ranging from 0 (not at all) to 10 (a great deal), was used for this question.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Respondents were asked “To what extent do you feel that your own personal actions can help prevent [coronavirus from spreading/climate change from worsening]” in order to measure respondents’ perceived efficacy (also known as ‘outcome expectancy’, Gregersen et al, 2021 ). A similar end-labelled 11-point scale, ranging from 0 (not at all) to 10 (a great deal), was used for this question.…”
Section: Methodsmentioning
confidence: 99%
“…It also matters whether a person feels able to take action and whether action will lead to certain outcomes, which are often collectively referred to as efficacy beliefs ( Bandura, 1995 ). Research has shown that efficacy beliefs are associated with changes in behaviour related to climate change ( Van Valkengoed and Steg, 2019 ) and may be a key factor in promoting action ( Gregersen et al, 2021 ). Research in Western democracies has found that high personal efficacy led to strong social distancing intentions and compliance with public health advice during the first wave of the coronavirus outbreak ( Duong et al, 2021 ; Jørgensen et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Anxiety does not always support withdrawal; it is in fact a well-recognized adaptive trait that can motivate threat response (Clayton, 2020). Indeed, there are many people whose distress about climate change motivates pro-climate action (Bouman et al, 2020), namely when those individuals also express personal efficacy (Gregerson et al, 2021). However, those individuals whose abilities to respond to their anxiety with positive action have already been compromised for various reasons are more likely to withdraw (Clayton, 2020;Navarro et al, 2021).…”
Section: Withdrawalmentioning
confidence: 99%
“…Firstly, efficacy beliefs are important antecedents of climate mitigation. Through analysis of a large European dataset, Gregersen et al (2021) show that -alongside feeling worried about climate change -personal efficacy, and beliefs about the outcomes of personal and collective responses, is associated with personal energy-saving behaviours. Bostrom et al (2019) found that self-efficacy and response-efficacy beliefs (related to collective and governmental responses) were associated with greater public support for climate mitigation.…”
Section: Why Efficacy Matters For Both Climate Mitigation and Adaptationmentioning
confidence: 99%
“…Nevertheless, this does not mean that specific efficacy variables should be discounted altogether for certain climate responses, as they may interact and function together as well. For instance, collective-efficacy may stimulate engagement in group action by increasing self-efficacy beliefs (Jugert et al 2016); and beliefs about personal and collective outcomes can be intercorrelated (Gregersen et al 2021). Perceptions about personal-level actions may therefore be associated with judgements about other people taking similar actions and the potential for greater impact when acting collectively.…”
Section: Why Efficacy Matters For Both Climate Mitigation and Adaptationmentioning
confidence: 99%